1988
DOI: 10.1016/0009-8981(88)90220-3
|View full text |Cite
|
Sign up to set email alerts
|

An immunobioluminescence assay for gamma-gamma enolase activity in human serum and cerebrospinal fluid

Abstract: SummaryA solid phase immunobioluminescence assay for the measurement of gammagamma enolase activity in human serum and cerebrospinal fluid is described. The assay combines the specificity of the antiserum with the specificity of measuring enolase activity, thus making the assay highly specific for gamma-gamma enolase. The sensitivity of the method allows determinations in unconcentrated cerebrospinal fluid samples. The new immunobioluminescence assay has been compared with a radioimmunoassay method. The correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Moreover c-src expression in neuroblastoma-and SCLC-cell lines correlated with neuroendocrine differentiation (Mellstrom et al, 1987) and c-src is connected to neurogenesis and neuronal differentiation (Brickel et al, 1991), as is the switch from a to y-enolase (Schmechel et al, 1980). In this connection it is very interesting that Wevers et al (1988) found in cerebrospinal fluid but not in serum from healthy individuals that 50% of NSE-ag had no enzyme activity. These data suggest that NSE-ag without enzyme activity may arise from inactivation of ychains and may be correlated with neuronal or neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover c-src expression in neuroblastoma-and SCLC-cell lines correlated with neuroendocrine differentiation (Mellstrom et al, 1987) and c-src is connected to neurogenesis and neuronal differentiation (Brickel et al, 1991), as is the switch from a to y-enolase (Schmechel et al, 1980). In this connection it is very interesting that Wevers et al (1988) found in cerebrospinal fluid but not in serum from healthy individuals that 50% of NSE-ag had no enzyme activity. These data suggest that NSE-ag without enzyme activity may arise from inactivation of ychains and may be correlated with neuronal or neuroendocrine differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…NSE has been suggested to be useful in distinguishing stroke from mimics, an important first step in expediting the diagnostic process [150][151][152]. As an alternative to antibody capture, POCTs based on fluid phase enzymatic activities [153,154] or semisolid phase bioluminescence [155] are used for plasma NSE monitoring.…”
Section: Cornell Universitymentioning
confidence: 99%
“…NSE has been suggested to be useful in distinguishing stroke from mimics, an important first step in expediting the diagnostic process [127,128,129]. As an alternative to antibody capture, POCTs based on fluid phase enzymatic activities [130,131] or semi-solid phase bioluminescence [132] are used for plasma NSE monitoring.…”
Section: Pocts Expedite Stroke Prognosticsmentioning
confidence: 99%